Highly Sensitive Detection Method of DICER1 Tumor Hotspot Mutations by Drop-off Droplet Digital PCR. (20th December 2021) - Vibert, Roseline; Gauthier-Villars, Marion; Carrière, Christelle; Dubois d'Enghien, Catherine; Cyrta, Joanna; Vincent-Salomon, Anne; Stoppa-Lyonnet, Dominique; Bièche, Ivan; Jeannot, Emmanuelle; Golmard, Lisa
Abstract: Background: DICER1 syndrome is an autosomal dominant inherited syndrome predisposing to various benign and malignant tumors, mainly occurring in children and young adults, requiring broad surveillance starting at birth with repeated irradiating imaging exams and sedations for young patients. It is caused by monoallelic germline pathogenic variants in the DICER1 gene. More than 90% of tumors bear an additional somatic DICER1 missense hotspot mutation, as a second hit, involving 1 of 6 codons clustered in exons 24 and 25. We designed and in vitro validated a drop-off droplet digital PCR (ddPCR) system to scan all DICER1 hotspot codons, allowing for a liquid biopsy test, an alternative to sedation and radiation exposure. Methods: Three drop-off ddPCR assays were designed, with 2 TaqMan probes per assay, 1 complementary to the wild-type sequence of the region containing hotspots and another 1 used as a reference . Eight tumor-derived DNAs and 5 synthetic oligonucleotides bearing DICER1 hotspot mutations were tested. Results: All tested mutations were detected, with a limit of detection ranging from 0.07% to 0.31% for codons p. E1705, p. D1709, and p. D1713 in exon 24 and from 0.06% to 0.15% for codons p. G1809, p. D1810, and p. E1813 in exon 25. Conclusions: The high sensitivity of this method is compatible with its use for plasma circulating tumor DNA (ctDNA) analysis for early tumor detection in DICER1 syndrome patients. It may reduce the need for radiation exposure and sedation in surveillance protocols and may also improve patient prognosis. Clinical trials are needed to evaluate ctDNA analysis in these patients.